HUBUNGAN POWER LENGAN DAN BAHU DAN KELENTUKAN DENGAN KECEPATAN RENANG 50 M GAYA KUPU-KUPU PADA ATLET PPLP RENANG PROVINSI RIAU - Wirastuti, Weni; Agust, Kristi; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The problem in this research is still lack the of swimming speed the usingbutterfly stroke in swimming athletes of PPLP Riau Province. It is assumed because lack ofmuscle power of arm and shoulder during arm movements attract (pull) and thrust (push),subtract away of the range ofrecovery time, less of increase in the hips above the water surfacefor waist flexibility giving influence away to thrust when doing dolphin so ittakes longer inusing a certain distance . The purpose of this study is to determine the relationship between thepower of arms and shoulders withflexibilityin the swimming speed of 50 meters using butterflystyle. This study is correlationally aims to find out how much the relationship betweenindependent and dependent variables. After that, the data normality test using Liliefors test withsignificance level α = 0.05 and normality test results obtained variable X1 = 0.162, variableand variable X2 = 0.150 Y = 0.179 with Ltabel (0.285), in other wordsit is the normaldistribution of data. Then continued by determine r by using product moment correlationanalysis, if rhitung>rtabel then there is a significant relationship. From the calculation of thecorrelation between the power of arm and shoulder muscles with the swimming speed obtainedrhitung = 0,880 while rtabel = 0.707. The results of correlation calculations between flexibilitywith swimming speed obtained while r table rhitung = 0.430 = 0.707. To determine thevariables R X1 and X2, the Y performed using double correlation formula, with rhitung(0.881)> rtable (0.707). So Ho rejected and Ha accepted. Thus, the conclusion is there is asignificant relationship between the arm and shoulder muscle power and flexibility with theswimming speed of 50 meters using butterfly style at the swimming PPLP athletes RiauProvince.Keywords: Power arm and shoulder muscles, flexibility, speed swimming 50m butterfly.